A study on conformal Ricci solitons and conformal Ricci almost solitons within the framework of almost contact geometry - S. Dey (Karpatsʹkì Matematičnì Publìkacìï, 2023)
The goal of this paper is to find some important Einstein manifolds using conformal Ricci solitons and conformal Ricci almost solitons. We prove that a Kenmotsu metric as a conformal Ricci soliton is Einstein if it is an $η$-Einstein or the potential vector field $V$ is infinitesimal contact transformation or collinear with the Reeb vector field $ξ$. Next, we prove that a Kenmotsu metric as gradient conformal Ricci almost soliton is Einstein if the Reeb vector field leaves the scalar curvature invariant. Finally, we have embellished an example to illustrate the existence of conformal Ricci soliton and gradient almost conformal Ricci soliton on Kenmotsu manifold.